Trends in mortality from lower respiratory infections in children under 14 years, 1990–2019: An analysis of the Global Burden of Disease Study 2019 - Xufei Xing; Siqi Tang; Weiye Wang; Haiyan Xiong; Tiejun Zhang; Weibing Wang; Yihan Lu; Tao Zhang; Chen Suo (Heliyon)
Background: Lower respiratory infections (LRIs) remain a leading cause of mortality among children, yet previous studies have primarily focused on children under 5 years of age as a whole, with limited research on more specific age groups. This study aimed to analyze the trends in mortality associated with lower respiratory infections (LRIs) among children under 14 years of age from 1990 to 2019, with particular attention to regional and age-specific disparities. Methods: We collected annual lower respiratory infection (LRI) deaths and mortality rates for six age groups of children under 14 years from 1990 to 2019 using data from GBD 2019. Estimated annual percentage changes (EAPCs) were calculated by fitting a linear regression model to quantify temporal trends. Additionally, EAPCs for 12 risk factors by Socio-Demographic Index（SDI） and age group were calculated to assess their impact on changes in LRI mortality. Results: Globally, LRI-related deaths among children under 14 years decreased by 68.81 %, from 2,290,115 (95 % UI 2,001,328 to 2,687,160) in 1990 to 714,315 (95 % UI 588,975 to 875,975) in 2019. The most substantial reduction was observed in East Asia, with an EAPC of −9.68 (95 % CI -9.98 to −9.38). The highest mortality occurred in the 28–364 days age group, with significant risk factors including child wasting (26.81 %), household air pollution from solid fuels (16.14 %), and low birth weight (10.15 %). In the low and lower-middle SDI regions, there was an upward trend in mortality due to ambient particulate pollution among children aged 10–14 years. Conclusion: Despite a significant global decline in LRI mortality among children under 14 years from 1990 to 2019, regional disparities persist. Addressing these inequalities and considering the developmental stages of children are crucial for further reducing child mortality rates.